2017
DOI: 10.1002/cpe.4110
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing rich content wikis with real‐time collaboration

Abstract: SUMMARYWikis are one of the most important tools of Web 2.0 allowing users to easily edit shared data. However, wikis offer limited support for merging concurrent contributions on the same pages. Users have to manually merge concurrent changes and there is no support for an automatic merging. Real-time collaborative editing reduces conflicts as the time frame for concurrent work is very short. In this paper, we propose extending wiki systems with real-time collaboration. We propose an automatic merging solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Several research efforts have already been reported on the possibilities of collaborative block-editing, Oster et al, 2006, Ignat et al, 2017, Martin et al, 2010, Davis and Ian, 2010 or other types of collaborative editing. Our research strategy is to explore existing concepts of collaborative editing, extend selected existing ideas with block editing, and provide a unified prototype.…”
Section: Block Editorsmentioning
confidence: 99%
“…Several research efforts have already been reported on the possibilities of collaborative block-editing, Oster et al, 2006, Ignat et al, 2017, Martin et al, 2010, Davis and Ian, 2010 or other types of collaborative editing. Our research strategy is to explore existing concepts of collaborative editing, extend selected existing ideas with block editing, and provide a unified prototype.…”
Section: Block Editorsmentioning
confidence: 99%
“…Human-to-human collaboration is becoming more and more critical in modern highly dispersed organizations and teams. Computer-supported collaborative systems enable geographically separated people working together to achieve a common goal through computer networks [1][2][3][4][5][6][7][8][9][10][11]. These systems provide strong technical supports for human-to-human collaboration [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%